Women's imprisonment in Eastern Europe : 'sitting out time' - Idrissi, Arta Jalili (Emerald studies in criminology, feminism and social change., 2023)
The field of prison studies has been dominated by an androcentric outlook, with little attention paid to women. Offering a unique theoretical fusion of the sociology of imprisonment, carceral geography, feminism and cultural criminology, Women's Imprisonment in Eastern Europe: 'Sitting out Time' examines how social, political, and cultural factors have shaped the development of gendered penal regimes in Eastern Europe and created an institutional battleground for opposing ideologies. Expanding from Latvia as a focal point, Arta Jalili Idrissi provides a current snapshot of women's imprisonment across the Global East. Understanding the situated and complex nature of the prison as an institution, she captures the interplay between the Soviet legacy and a neoliberal agenda within three distinct realms of punishment: spatial, procedural and relational. Revealing clashes within the prison environment, as well as their broader socio-political and ideological contexts, Jalili Idrissi also exposes the specific nuances of gender implications. The first qualitative study based on an ethnographic approach to women's carceral experiences in Latvia, Women's Imprisonment in Eastern Europe: 'Sitting out Time' draws parallels across Eastern Europe and throughout the neoliberal West to provide a refreshing and timely addition to the study of criminology and the sociology of imprisonment.